Etiek en etos in Romeine - Du Toit, A (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
Ethics and Ethos in Romans Anticipated ethos in Romans focuses on the way in which Paul, through various ethical indicators, hoped to influence the existing life style of his addressees.The introductory verses of chapter 12 are crucial and set the tone for all his parenesis. Apart from some general directives, Paul finds it necessary to deal with certain Concrete issues. The Christians in Rome faced some uncertainties regarding right behaviour towards their Roman authorities. It also seems beyond question that there was tension between (certain) Jewish and non-Jewish Christian groups. Evidently, Paul does not concentrate on issues dividing the strong and the weak, but on the way in which they handle their differences. For this purpose, he activates several ethical indicators, inter alia accepting and respecting one another in love, the example of Jesus Christ, glorifying God, the upbuilding of the church and the reaction of outsiders. In a final section two present day issues are addressed: The need for a renewed God-orientation in the church, and the way in which the discussion on homosexuality is handled within the Dutch Reformed Church.